Speciation along a shared evolutionary trajectory. Issue 6 (10th May 2016) - Dochtermann, Ned A.; Matocq, Marjorie D.
Abstract : Groups of organisms—whether multiple species or populations of a single species—can differ in several non-exclusive ways. For example, groups may have diverged phenotypically, genetically, or in the evolutionary responses available to them. We tested for the latter of these—response divergence—between 2 species of woodrats: Neotoma fuscipes and Neotoma macrotis . Based on random skewers analyses we found that, despite being well differentiated both phenotypically and genetically, N. fuscipes and N. macrotis appear to be diverging along a shared evolutionary trajectory ( r°  = 0.895, P =  0.114). Because these species are currently in secondary contact, their phenotypic evolution being along a shared evolutionary axis has important implications. In particular, that their response to selection arising from interspecific interactions will be constrained along the same evolutionary trajectory may reduce the potential for reinforcing selection to maintain species boundaries.